COMUNICAREA ŞTIINŢIFICĂ ÎN CONTEXTUL ACCESULUI DESCHIS LA INFORMAŢIE: (autoreferatul tezei de doctor habilitat în sociologie) - ŢURCAN, Conf. univ. dr. hab., Universitatea de Stat din Moldova, Nelly (BIBLIOPOLIS, 2020)
Aim of the thesis: Trends determination of the evolution of scientific communication, elucidate and analyze features of scientific communication process in the context of open access to information. Objectives of the thesis: revealing the essence of scientific communication; analysis of the traditional paradigm of scholarly communication and transformation of the paradigm under Open Access; research of the policies and strategies of Open Access to scientific information; social assessment of scientific communication system transformations; assessing the crisis effects of scholarly communication system; studying the mechanism of scientific communication through the scientific journals system of the Republic of Moldova; studying the perception of the scientific communication role for the scientific community of the Republic of Moldova; clear up the role of libraries as social factor in the scientific communication process; emphasizing the impact of Open Access on expanding the visibility of science and social interactions through citations. Basically new obtained results for science and practice: multidimensional examination of the scientific communication phenomenon; development of the scientific communication model in the context of Open Access; scientific demonstration of the Scientific Communication and the determination of a new direction of research in Communication Science. Theoretical significance of the thesis lie in the conceptualization of the scientific communication phenomenon and the scientific communication innovative paradigm, based on Open Access; in the development of a new scientific communication model, based on the concept of Open Access; in the creating of the explanatory theoretical framework for scientific communication in the context of changes in the distribution and the access to the scientific information; in the identification of the scientific communication as a new direction of research in communication science. Practical value of the paper consists in use of the recommendations that will allow to improve the scholarly communication system in the Republic of Moldova by implementing Open Access strategies. The study results can serve as a methodological foundation for the open access institutional policy and for the implementation of alternative methods of publication and access to scientific information. Implementation of the scientific results: The scientific research results have been applied to promote innovative models of dissemination and access to scientific information. The conclusions and recommendations presented in this thesis the have been applied to develop strategies for the development of the institutional repositories in several universities of the country. In addition, this study underlies some university courses.